Pendampingan Digital Marketing untuk Meningkatkan Penjualan UMKM Kue Kering di Gresik - Farida, Eka; Hidayat, Taufiq (IKIP PGRI Bojonegoro, 2024)
MSMEs are business activities that are able to expand employment opportunities for the community and encourage economic growth. The aim of this service is to provide digital marketing assistance to pastry business people to develop their business so that their productivity will increase. Each existing MSME, especially those operating in the dry cake home industry, is faced with various problems. One of the MSMEs that already has a sales market share is the right choice for assistance because many have fundamental problems in the marketing sector. These MSMEs have several problems, namely they don't have a product brand, don't have a logo and product label, and don't do digital marketing. Based on this problem, our target is to help pastry MSMEs in the Gresik area through digital marketing assistance to increase sales of pastry products. The results of the service show that these MSMEs have product brands, logos and marketing accounts on social media and the Tokopedia marketplace.